Household energy and water practices change post-occupancy in an Australian low-carbon development - Breadsell, Jessica; Byrne, Joshua; Morrison, Greg (MDPI, 2019)
© 2019 by the authors. This research comprises a longitudinal study of a cohort of residents moving into a low-carbon development and their pre- and post-occupancy household practices that consume energy and water. They are the early adopters of living in low-carbon households and provide valuable insight into the influence of design and technology on household practices. Household energy and water consumption levels are measured and normalised to the metropolitan average to discuss the influence of design and technology on use. Heating, cooling and showering practices consume the largest proportion of household energy and water use and so the changes to thermal comfort and personal hygiene practices are examined along with a consideration of the influence of lifestyle and family composition on cooling practices. Household water and energy use decreases due to technology and design influences post-occupancy. However, the personal practice history of residents influences water and energy consumption. Changes to the meaning element of personal hygiene practices show how these are interlocked and unlikely to change in their duration when there are other demanding practices to be undertaken.